Pengaruh Due Professional Care, Kompleksitas Tugas dan Good Governance Terhadap Kinerja Auditor Pada Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Provinsi Aceh - Dy Ilham Satria (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2017)
The purpose of this research was to examine the influence of Due professional care, Duty complexity, and Good governance toward the Auditor performance at BPK-RI of Aceh Province representative. The population of this research was all auditors at BPK-RI of Aceh Province representative consisted of 69 respondents. The data used in this research was primary data obtained by distributing questionnaires to all Auditor at Financial Audit Agency inspectors of Aceh Province representative. The method of data analysis was quantitative analysis by using validity test, reliability test, and classical assumption test that consisted of normality test, mutlicolinearity and heterokedasticity test. The result of this research indicated that Due professional care influenced positively on the Auditor performance with t-count 2.030 >table 1.668 and the significance value was 0.046 < 0.05, duty complexity influenced positively on the Auditor performance with t-count was 4.444 > t-table 1.668 and the significance value was 0.017 < 0.05, and Good governance did not influence on the Auditor performance with t-count1.448 < t-table 1.668, and the significance value was 0.152 > 0.05. Simultaneously, Due professional care, duty complexity, and good governance influenced on the Auditor performance at Financial Audit Agency inspectors of Aceh Province representative with the result of f-count was 55.208, while f-table was at 95% of confidence level obtained f-table 5% + 2.75 or f-count>f-table.